Reflections on the beginnings of Linguistics at Tribhuvan University - Hale, Austin (Nepalese Linguistics, 2019)
The definitive account of the birth and development of linguistics, and of the study of minority languages in Nepal has yet to be written. In this brief account we focus on the part of that development that arose from interactions between SIL and Tribhuvan University in the late 1960’s and early 1970’s.